Descriptions of ten known species of the superfamily Mononchoidea (Mononchida: Nematoda) from North India with a detailed account on their variations - Tahseen, Qudsia; Asif, Mohammad; Mustaqim, Malka; Ahlawat, Shikha; Bert, Wim (Zootaxa, 2013)
Ten species of the superfamily Mononchoidea from fourteen populations collected during a survey of terrestrial and fresh-water habitats of North India, are described and illustrated. The species include Clarkus papillatus (Bastian, 1865) Jaira-jpuri, 1970, Prionchulus muscorum (Dujardin, 1845) Wu & Hoeppli, 1929, Mylonchulus contractus Jairajpuri, 1970, M. hawaiiensis (Cassidy, 1931) Andrássy, 1958, M. lacustris (Cobb in Cobb, 1915) Andrássy, 1958, M. minor (Cobb, 1893) Andrássy, 1958, M. obtusicaudatus (Daday, 1899) Andrássy, 1958, M. vasis Yeates, 1992, Sporonchulus ibitiensis (Car-valho, 1951) Andrássy, 1958 and S. vagabundus Jairajpuri, 1971. Mylonchulus vasis Yeates, 1992 is reported for the first time from India. The variable, as well as the relatively consistent characters are discussed in different populations to assess their role in the diagnosis of species.